MARINE TRANSPORTATION ACROSS INDONESIA AND SINGAPORE IN TRANSNATIONAL CHINA BATAM TRANSPORTASI LAUT INDONESIA- SINGAPURA DALAM JARINGAN TRANSNASIONAL - Danny Faturachman; C. Dewi Hartati; Febi Nur Biduri; Hin Goan Gunawan (Bambuti, 2021)
Batam City, which is part of the Riau Islands province, is a connecting city between Indonesia and Singapore. Batam City is located in a very strategic location in the border region between countries, neighboring one of the world's business centers, namely Singapore. For this reason, marine transportation has a very important role in maritime countries like Indonesia. The high intensity of Batam and Singapore transportation cannot be separated from the Chinese population of Batam which is a community group in the city of Batam. The existence of Batam Chinese has been going on for centuries, since they came from mainland China using boats. With tenacity, social networks and geographical proximity to Singapore, Batam Chinese people become dominant in the economy in Batam. This study seeks to show maritime aspects and shipbuilding technology and their relationship with social society through transnational concepts. With globalization, and to develop networks, people really need sea transportation to support the transnational process. For all that, maritime safety is needed which greatly affects the sustainability development efforts, especially sea transportation activities.